Economic Resilience of German Lignite Regions in Transition - Nora Stognief; Paula Walk; Oliver Schöttker; Pao-Yu Oei (sustainability, 2019)
This paper recalls the development of the German lignite regions Rhineland and Lusatia since 1945 to allow for a better understanding of their situation in 2019. We analyze their economic resilience, defined as adaptive capacity, using Holling's adaptive cycle model. We find that the Rhineland is currently in the conservation phase, while Lusatia experiences a reorganization phase following the economic shock of the German reunification. Key policy recommendations for the upcoming coal phase-out are to foster innovation within the Rhineland's infrastructures to avoid overconnection, and to expand digital and transportation infrastructure in Lusatia so that the structurally weak region can enter the exploitation phase. Future policymaking should take into consideration the differences between the two regions in order to enable a just and timely transition during which lasting adaptive capacity can be built.
Keywords: 330; coal phase-out; energy transition; coal transition; sustainability transition; Energiewende; just transition; structural change; regional economic resilience; adaptive cycle model; Germany